Indian Medicinal Plants An Illustrated Dictionary - Khare, C.P (Springer New York : Imprint: Springer, 2007)
In an easy to use dictionary style of A-Z presentation, this volume lists the taxonomy and medicinal usage of Indian plants. Also given are both traditional Indian and international synonyms along with details of the habitats of the plants. Indian Medicinal Plants. An Illustrated Dictionary is aimed at bringing out an updated Acute Study Dictionary of plant sources of Indian medicine. The text is based on authentic treatises which are the outcome of scientific screening and critical evaluation by eminent scholars. Readers, if they so desire, can always refer back to a particular research paper cited in the original source. The text is illustrated by over 550 full-color figures.